The role of collagen type VI alpha 6 chain as a potential tumor suppressor in breast cancer: an immune regulation perspective - Jian-Di Li; Li-Li Deng; Jia-Yuan Luo; Chao-Hua Mo; Bang-Teng Chi; Wan-Ying Huang; Rong-Quan He; Di-Yuan Qin; Chang Song; Wen Zou; Gang Chen (BMC Cancer)
Abstract Background Collagen type VI alpha 6 chain (COL6A6), an essential component of epithelial cell basal lamina, is hypothesized to function as a tumor suppressor in various cancers, yet its role in breast cancer remains unclear. This study aimed to elucidate COL6A6 expression patterns, assess its impact on the tumor immune microenvironment, and uncover underlying molecular mechanisms in breast cancer progression. Methods Immunohistochemical staining of COL6A6 was conducted on 136 breast cancer tissues and 50 non-breast-cancer controls in-house. Global microarray and high-throughput sequencing datasets were analyzed to confirm mRNA expression trends, supported by single-cell RNA sequencing for expression intensity and distribution. Prognostic evaluation utilized a multicenter cohort of breast cancer patients through Kaplan–Meier survival and decision curve analyses. Tumor deconvolution and gene set enrichment analyses predicted COL6A6’s association with the tumor immune microenvironment and its molecular mechanisms. Mouse models, spatial transcriptomic sequencing, and transcriptional regulation analyses were employed to elucidate the intimate relationship between COL6A6 expression and immune cell distribution. Potential therapeutic agents for breast cancer patients were predicted by targeting the COL6A6 protein. Results COL6A6 protein staining intensity was significantly lower in breast cancer tissues compared to normal breast tissues (p < 0.0001). Integrated analysis confirmed COL6A6 downregulation in 4818 breast cancer tissues versus 1236 non-breast-cancer tissues (standardized mean difference =  − 1.27 [− 1.66, − 0.87]), supported by single-cell RNA sequencing. Reduced COL6A6 mRNA expression moderately discriminated breast cancer from non-breast-cancer tissues (pooled area under the curve = 0.88, sensitivity = 84.85%, specificity = 72.68%). Decreased COL6A6 expression correlated with poorer overall and relapse-free survival. It had a negative correlation with the purity of the tumor but a positive correlation with the quantity of stromal and immune cells in the tumor microenvironment. Immune regulatory pathways such as adaptive immune response, T cell differentiation, T cell proliferation, macrophage activation, and natural killer cell-mediated cytotoxicity were associated with the gene sets that were enriched in the analysis. Immune-related biological processes, such as immunoglobulin production, generation of immune response mediators, myeloid leukocyte activation, leukocyte chemotaxis, and neutrophil migration, were significantly enriched in mouse models immunized with a COL6A6 peptide vaccine. The downregulation of COL6A6 was associated with reduced immune cell infiltration in malignant regions of breast cancer tissue slices, which might be negatively regulated by the CBX2 transcription factor. MK-886 may serve as a promising therapeutic agent for breast cancer treatment by targeting COL6A6 (Vina score =  − 8.0). Conclusions COL6A6 may operate as a tumor suppressor in breast cancer, underscoring its correlation with immune activity in the tumor microenvironment. These findings suggest COL6A6 as a promising therapeutic target and prognostic biomarker warranting further investigation.